Pentingnya Karakter Di Lingkungan Kampus - Bate’e, Mashati; Hulu, Destin Cerah Anggela; Lase, Natalia Kristiani (CV. SINAR HOWUHOWU, 2025)
Character is an important aspect that influences the development of an individual's personality in the campus environment. As a place for intellectual, social, and emotional growth, the campus plays a strategic role in shaping students' character. Good character not only supports academic success but also shapes students' attitudes and behaviors in their social lives. In the campus environment, students are faced with various challenges that test their morals and ethics, such as plagiarism, substance abuse, and violations of rules. Therefore, it is important to develop a strong and positive character through integrated character education in campus activities. Character enhancement can be achieved through both formal and non-formal learning, as well as an environment that supports the formation of such character. With good character, students will be able to face life's challenges wisely and contribute positively to society.